Thermal Denaturation of Molten Globule State of Cytochrome c Induced by High Concentration of Sodium Dodecyl Sulfate - CHAMANI, J. (Asian Journal of Chemistry, 2010)
The molten globule state can be an intermediate in the protein folding pathway; thus; its detailed description can help understanding protein folding. Sodium dodecyl sulfate (SDS), an anionic surfactant that is commonly used to mimic hydrophobic binding environments such as cell membranes is known to denature some native state proteins, including horse cytochrome c (cyt c). In this article, thermal denaturation of acid denatured cyt c is studied under the influence of SDS to form molten globule like states at above the critical micelle concentration using circular dichroism, ultraviolet and visible absorption as well as fluorescence. Thermal denaturation experiments show that cyt c-SDS complexes with large [SDS]/[cyt] have similar thermal behaviour in both low and neutral pH, suggesting negligible pH effect under these conditions. The protein or SDS absolute concentration is an important factor in addition to the [SDS]/[cyt] ratio in determining the thermal behaviour of the protein-surfactant complex, as monitored by far-UV CD and fluorescence. The results suggest that the protein chain wraps around the micelle at about 20 mM SDS, whereas the micelle nucleates on the protein hydrophobic sites at higher concentration.